OP0187 Transgenic disruption of glucocorticoid-signaling in mature osteoblasts and osteocytes attenuates structural bone damage in a long-term murine k/bxn serum-induced arthritis model. (15th June 2017) - Wiebe, E; Spies, C; Tu, J; Maleitzke, T; Zhang, Y; Seibel, M; Zhou, H; Buttgereit, F
Abstract : Background: The role of endogenous glucocorticoids (GC) in bone metabolism in chronic inflammatory arthritis remains unclear. We have previously shown that disruption of GC-signaling in osteoblasts results in a marked attenuation of arthritis in the K/BxN serum-induced and CAIA mouse model with preservation of bone volume and structure 1, 2 . Objectives: In order to investigate the impact of endogenous GCs on bone erosion and turnover in chronic inflammatory arthritis, we now studied the effects of disrupted osteoblastic GC-signaling in a long-term murine arthritis model. Methods: Intracellular GC-signaling in osteoblasts was disrupted by transgenic overexpression of 11beta-hydroxysteroid dehydrogenase type 2 (11β-HSD type 2) under the control of a type 1 collagen promoter. Arthritis was induced in 5-week old male transgenic (tg) mice and their wild-type (WT) littermates. In order to maintain a chronically active arthritis, mice were boosted on day 14 and 28 by subcutaneous injection of K/BxN serum, controls (CTR) received PBS, respectively. Severity of arthritis was assessed daily by clinical scoring and ankle size measurements until the endpoint (day 42). Ankle joints were assessed by a histopathologic score and microfocal computed tomography (micro-CT). Systemic effects of inflammation on bone metabolism were quantified by histomorphometry and micro-CT of the tibia. Results: Acute Arthritis developed in both tg and WT mice and remained active over the period of 42 days, with a reduced, yet non-significant, severity in tg compared to WT mice. Histological indices of inflammation, cartilage damage and especially bone erosion, additionally assessed by micro-CT, tended to be overall reduced in tg mice, yet not reaching a level of significance. Bone volume and bone turnover did not differ between tg and WT arthritic mice. Conclusions: The modulating effect of disrupted GC-signaling in osteoblasts in serum-induced autoimmune-arthritis prevails in a chronic inflammatory setting, leading to less severe local inflammation and bone destruction. This supports the important role of endogenous GCs for an intact bone metabolism in inflammatory bone disease. References: Tu J, Zhang Y, Kim S, Wiebe E, Spies CM, Buttgereit F, et al. Transgenic Disruption of Glucocorticoid Signaling in Osteoblasts Attenuates Joint Inflammation in Collagen Antibody-Induced Arthritis. Am J Pathol. 2016;186(5):1293–301. Buttgereit F, Zhou H, Kalak R, Gaber T, Spies CM, Huscher D, et al. Transgenic disruption of glucocorticoid signaling in mature osteoblasts and osteocytes attenuates K/BxN mouse serum-induced arthritis in vivo. Arthritis Rheum. 2009;60(7):1998–2007. Disclosure of Interest: None declared